Biomedical Applications: Liver‐Specific and Echogenic Hyaluronic Acid Nanoparticles Facilitating Liver Cancer Discrimination (Adv. Funct. Mater. 44/2013). (26th November 2013) - Min, Hyun Su; Son, Sejin; Lee, Tae Woong; Koo, Heebeom; Yoon, Hong Yeol; Na, Jin Hee; Choi, Yongseok; Park, Jae Hyung; Lee, Jaeyoung; Han, Moon Hee; Park, Rang‐Woon; Kim, In‐San; et al.
<x xml:space="preserve">Abstract</x> On page 5518, an ultralong‐acting, liver‐specific, ultrasound contrast agent is presented in the form of self‐assembled, echogenic hyaluronic acid nanoparticles. I. C. Kwon, K. Kim, and co‐workers use hydrophobic interactions and an oilin‐water emulsification method to encapsulate bioinert and hydrophobic perfluoropentane as an ultrasound gas precursor into the nanoparticles. These particles are more stable and robust echogenic solid bodies than the conventional microbubbles, with an in vivo favorable hydrodynamic size. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>